CFD Analyses of Density Gradients under Conditions of Supersonic Flow at Low Pressures - Bayer, Robert; Bača, Petr; Maxa, Jiří; Šabacká, Pavla; Binar, Tomáš; Vyroubal, Petr (Sensors (Basel, Switzerland), 2024)
This paper deals with CFD analyses of the difference in the nature of the shock waves in supersonic flow under atmospheric pressure and pressure conditions at the boundary of continuum mechanics for electron microscopy. The first part describes the verification of the CFD analyses in combination with the experimental chamber results and the initial analyses using optical methods at low pressures on the boundary of continuum mechanics that were performed. The second part describes the analyses on an underexpanded nozzle performed to analyze the characteristics of normal shock waves in a pressure range from atmospheric pressure to pressures at the boundary of continuum mechanics. The results obtained by CFD modeling are prepared as a basis for the design of the planned experimental sensing of density gradients using optical methods, and for validation, the expected pressure and temperature courses from selected locations suitable for the placement of temperature and pressure sensors are prepared from the CFD analyses.
Keywords: Ansys Fluent; CFD; nozzle; shock wave; critical flow; ESEM; Schlieren method